Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1017/s0007114519002125
|View full text |Cite
|
Sign up to set email alerts
|

Irregularity in breakfast consumption and daily meal timing patterns in association with body weight status and inflammation

Abstract: Irregular breakfast consumption and food timing patterns in relation to weight status and inflammation were investigated in a cross-sectional manner among 644 participants in the Cancer Prevention Study-3 Diet Assessment Sub-study. Breakfast consumption, and the individual means and the intra-individual standard deviation (isd) of time at first intake of the day, duration of daily intake window and midpoint of daily intake window were collected via six 24-h recalls and examined in relation to BMI, waist circum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…For example, a long overnight fasting period (>18 h) has been associated with a relative decrease in body-mass index (BMI) [2]. However, a study among women in the 2009-2010 U.S. National Health and Nutrition Examination Survey (NHANES) showed a significant bivariate relationship between longer overnight fasting and higher BMI [3], and a similar finding of a correlation between a shorter diet intake window (i.e., longer fasting) and higher waist circumference was reported in the Cancer Prevention Study-3 Diet Assessment sub-study [14]. Moreover, multiple pilot intervention studies examined the effects of time-restricted feeding, otherwise known as time-restricted eating, or restricting caloric intake to a consistent window of <12 h per day, on weight loss.…”
Section: Introductionmentioning
confidence: 83%
“…For example, a long overnight fasting period (>18 h) has been associated with a relative decrease in body-mass index (BMI) [2]. However, a study among women in the 2009-2010 U.S. National Health and Nutrition Examination Survey (NHANES) showed a significant bivariate relationship between longer overnight fasting and higher BMI [3], and a similar finding of a correlation between a shorter diet intake window (i.e., longer fasting) and higher waist circumference was reported in the Cancer Prevention Study-3 Diet Assessment sub-study [14]. Moreover, multiple pilot intervention studies examined the effects of time-restricted feeding, otherwise known as time-restricted eating, or restricting caloric intake to a consistent window of <12 h per day, on weight loss.…”
Section: Introductionmentioning
confidence: 83%
“…Habitually skipping breakfast has also been associated with higher odds of having chronic inflammation. Recently, one cross-sectional study including 644 participants in the Cancer Prevention Study-3 Diet Assessment Sub-study assessed breakfast consumption and inflammatory status using glycoprotein acetyl as the inflammatory indicator (12) . Individuals who ate breakfast for 5 d had higher glycoprotein acetyl (β 0•21; 95 % CI 0•03, 0•40) when compared with those who consumed breakfast on all 6 d. However, no association was found for other exposure groups, which could be due to the small sample size of those groups (12) .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, all of the aforementioned chronic conditions or diseases are associated with chronic inflammation (6,(8)(9)(10) . Two recent cross-sectional studies reported that consumption of breakfast foods was associated with lower inflammation, assessed via serum C-reactive protein (CRP) (11) or glycoprotein acetyls (12) . However, these studies were limited by an indirect assessment of breakfast consumption (11) or a small sample size (n 644) (12) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, irregular breakfast consumption was indicated to be associated with higher inflammation levels. 35 Higher levels of inflammatory cytokine are associated with weaker grip strength. 36 Thus, this may also be an explanation.…”
Section: Discussionmentioning
confidence: 99%